Strategi Efektif Bertahan dan Berkembang di Dunia Akademik dan Kerja - Dina Novita; Karina Mayani; Pramesti Cahyani; Raetha Destriyani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service activity was conducted to respond to the growing need for high school students to prepare themselves for both academic and professional challenges after graduation. The program aimed to strengthen students’ understanding of self-readiness as they plan to continue their studies while working. The activity was held at SMK Perguruan Rakyat 1 Jakarta on 31 October 2025 and involved 16 lecturers and students from Universitas Pamulang as facilitators, with 50 twelfth-grade students as participants. The implementation followed three stages: preparation, execution, and reporting. During the execution stage, the facilitators delivered learning materials through presentations, practical sessions, discussions, and question-and-answer activities designed to build students’ confidence, awareness of workplace expectations, and strategies for academic–work balance. The results indicate that participants gained clearer insight into managing time, developing soft skills, adapting to academic demands, and preparing for early career challenges. Students also expressed increased motivation to pursue higher education while working and felt better equipped to make informed decisions about their future pathways. Overall, the program successfully enhanced students’ readiness to transition into both academic and professional environments.